Elevated plasma glucagon-like peptide 1 and 2 concentrations in ileum resected short bowel patients with a preserved colon. Issue 3 (1st September 2000) - Jeppesen, P B; Hartmann, B; Thulesen, J; Hansen, B S; Holst, J J; Poulsen, S S; Mortensen, P B
Abstract : BACKGROUND: The glucagon-like peptides (GLP) 1 and 2 are secreted postprandially from L cells located mainly in the ileum. Both hormones prolong intestinal transit and GLP-2 is intestinotrophic in rodents. Patients with a jejunostomy have poor adaptation, rapid gastric and intestinal transit, and impaired postprandial GLP-2 secretion. Ileum resected short bowel patients with a preserved colon show evidence of functional adaptation and have normal gastric emptying. AIM: To investigate if GLP-1 and GLP-2 contribute to the positive effects of a preserved colon in short bowel patients by measuring circulating levels of GLP-1 and GLP-2 in seven ileum resected short bowel patients with a preserved colon and seven age and sex matched controls. METHODS: GLP-1 and GLP-2 immunoreactivity was measured by specific radioimmunoassays in plasma collected at fasting and at regular intervals 180 minutes after a test meal. RESULTS: Median (25–75%) fasting GLP-2 values were 72 (69–105) pmol/l versus 23 (19–27) pmol/l (p=0.001) and meal stimulated area under the curve was 21 078 (14 811–26 610) min×pmol/l versus 11 150 (7151–12 801) min×pmol/l (p=0.01) in short bowel patients with a preserved colon compared with control subjects. Fasting GLP-1 values were 10 (6–12) pmol/l versus 5 (3–5) pmol/l (p=0.01) and meal stimulated area under the curve was 3418 (2966–6850) min×pmol/l versus 2478 (1929–3199) min×pmol/l (p=0.04), respectively. CONCLUSION: Ileum resected short bowel patients with a preserved colon had elevated fasting plasma concentrations of GLP-1 and GLP-2 and significantly larger meal stimulated areas under the curve compared with age and sex matched controls. Elevated GLP-1 and GLP-2 concentrations may contribute to the positive effects of a preserved colon on intestinal motility and functional adaptation in ileum resected short bowel patients.